Perceived Organizational Support Effects On Organizational Trust And Teacher Performance: Job Satisfaction As Moderator - Amaliyana Tendriawaru Anas (PT PUSTAKA CENDEKIA GROUP, 2025)
This study uses a quantitative approach with an explanatory design to test the causal relationship between variables in the context of secondary school teachers in Kendari City. The research population includes teachers in public and private schools, with the determination of the sample using a simple random sampling technique so that all members of the population have the same opportunity to be selected. Data was collected through a survey using a five-point Likert scale closed questionnaire to measure Perception of Organizational Support, Organizational Trust, Job Satisfaction, and Teacher Performance based on tested indicators. Before the analysis is carried out, the research instrument is first tested for validity and reliability so that the measurements produced are accurate and consistent. Data analysis was carried out using statistical software-assisted path analysis to identify the direct influence between variables and test the role of job satisfaction as a moderation variable. The results of the study show that the perception of organizational support has a significant effect on organizational trust. These findings indicate that teachers who feel that schools provide care, support, and fair treatment tend to have stronger beliefs in institutions. In addition, the perception of organizational support also has a significant effect on teacher performance, which indicates that a supportive work environment encourages teachers to work more optimally. This study also proves that organizational trust has a significant effect on teacher performance, so trust is an important factor in encouraging motivation, commitment, and quality of task implementation. On the other satisfaction has not been shown to have a significant direct effect on teacher performance. However, job satisfaction has been shown to strengthen the relationship between organizational trust and teacher performance, so the influence of trust on performance will be stronger when teachers feel satisfied with their work.